THE CRYSTAL CHEMISTRY OF FERSMANITE, CA4 (NA, CA)4 (TI, NB)4 (SI2O7)2 O8 F3 - Sokolova E.; Hawthorne F.C.; Khomyakov A.P. (My University, 2002)
Fersmanite, Ca-4(Na,Ca)(4)(Ti4+,Nb)(4) (Si2O7)(2) O-8 F-3, is the only mineral with an isolated layer of corner-sharing ({Ti4+,Nb}O-6) octahedra. The crystal structure of fersmanite from the Khibina alkaline massif, Kola Peninsula, Russia, monoclinic, a 10. 183(2), b 10.183(2), c 20.396(4) Angstrom, beta 97.19(3)degrees, V 2098.2(2) Angstrom(3), space group C2/c, Z = 4, D(calc.) = 3.159 g.cm(-3), was refined to an R index of 4.1% based on 2119 observed [F-degrees > 4sigmaF] unique reflections measured with MoKalpha X-radiation on an automated four-circle diffractometer equipped with a CCD detector. There are two Si sites occupied solely by Si and tetrahedrally coordinated by four O atoms, and two octahedrally coordinated M sites containing Ti4+ and Nb. There are four A sites occupied by Ca and Na: the A(1) and A(2) sites are [6]-coordinated and contain Ca and very minor Fe2+ + Mn2+; the A(3) and A(4) sites are [8]-coordinated and contain dominant Na, major Ca and very minor Sr. Each (MO6) octahedron shares two trans vertices with two other octahedra to form a 7 Angstrom [MO5] chain. These chains extend along [110] and [1 (1) over bar0], and intermesh to form a layer parallel to (001); where the chains intersect, an [M4O18] cluster occurs; it is the fundamental building block of the layer. In this cluster, each (MO6) octahedron shares three corners with other (MO6) octahedra, forming a vacant octahedron inside the cluster. The [8]-coordinated A cations fill cages within the layer. The [M4O16] layers decorated with (Si2O7) groups alternate with sheets of (AO(6)) octahedra along the c direction. The structures of fersmanite and pyrochlore, (CaNa) Nb-2 O-6 (OH,F), are based on the same type of [M4O18] cluster.
Keywords: Ti silicate; fersmanite; crystal-structure refinement; pyrochlore; Khibina–Lovozero complex; Kola Peninsula; Russia